L’ensemble gallo-romain de Donnery “ le Murger ” (Loiret) - Laurent Fournier (Revue Archéologique du Centre de la France)
An urgent archaeological rescue operation was carried out in Donnery (Loiret) following the discovery by Mr. Gérard Héau of Gallo-Roman tiles and ceramics on the construction site of a residence for the elderly at the place known as “le Murger”. The earthworks had affected a large part of the site and only the remains of the western part were partially preserved. After a quick assessment, a five-week excavation was undertaken with a small team. The buildings uncovered belong to a large Gallo-Roman complex, perhaps complementing the discoveries made in 1978 by Jean-François Baratin near the church.